An observational analysis of climbing an obstacle in mountain biking: A case study - Iglesias, A.; Lapresa, D.; Dalmau, J. M.; Anguera, M. T. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
An observation system has been designed within observational methodology that permits analysis and intervention in the technical action of climbing an obstacle in mountain biking. Using records that correspond to the performance of an elite athlete, the ideal technique for climbing an obstacle has been inferred. Data collection and coding was done using LINCE software. The reliability of the observation system was guaranteed via intra-observer concordance, using Cohen`s Kappa coefficient. The generalisability analysis carried out has guaranteed the homogeneity of the records and the validity of the observation instrument. The data packages obtained detail the behaviour of the cyclist in each observed technical action. Through a lag sequential analysis, regularities were found in performance technique, establishing four fundamental phases and nuances that characterise the action in detail at the start and end of the phases: pedal stroke, handlebar pull, hip push and stabilisation.